Tindak Tutur dan Strategi Bertutur dalam Pasambahan Maantaan Marapulai Pesta Perkawinan di Alahan Panjang Kabupaten Solok - Rosnilawati, Rosnilawati; Ermanto, Ermanto; Novia, Novia (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written that has purpose to (1) describethe form of speech acts at the pasambahan maanta marapulai wedding feast inKenagarian Alahan Panjang Kabupaten Solok, and (2) Strategy tells the pasambahan maanta marapulai wedding feast onKenagarian Alahan Panjang Kabupaten Solok. The data of this research is a form of speech act and the strategy tells the pasambahan maanta marapulai wedding feast onKenagarian Alahan Panjang Kabupaten Solok. Sources of research data from recordings spoken by the speaker (juaro) inKenagarian Alahan Panjang Kabupaten Solok. The findings of this study as follows. First, there are four forms of speech acts are used inpasambahan maanta marapulai, namely (1) representative, (2) directive, (3) expressive, (4) declaration. Second, the strategy used in the recalledpasambahan maanta marapulai, namely (1) tells forthright without further ado, (2) tells forthright with niceties positive politeness, (3) tells forthright with negative politeness, and (4) vaguely recalled vague.